Implementation of The Project Based Learning Model in Science Learning To Improve Scientific Literacy on The Issue of Global Climate Change - Nugroho, Purwo Adi; Dewi, Naomi Dias Laksita (PT. Anagata Sembagi Education, 2025)
Global climate change is a pressing issue that demands scientific literacy among young people to enable them to understand, analyze, and formulate scientifically based solutions. However, the low scientific literacy achievement of Indonesian students based on the PISA results indicates the need for pedagogical innovation in science learning. This study aims to examine the relevance of Project Based Learning (PjBL) in improving scientific literacy through the integration of climate change issues. The method used is a qualitative literature review approach of scientific articles, books, and research reports from the last ten years. Data analysis was carried out through reduction, presentation, and synthesis of findings to confirm the connection between PjBL, scientific literacy, and climate change issues. The results of the study indicate that PjBL effectively encourages active, collaborative, and experience-based learning that is relevant to global challenges. This model develops critical thinking skills, scientific communication, and ecological awareness through real-life projects such as waste management, reforestation, and experiments on the greenhouse effect. The theoretical implications are aligned with constructivism and the inquiry approach, while the practical implications include the transformation of teacher roles, authentic assessment, and applicable curriculum design. Despite constraints on facilities and teacher competencies, collaborative strategies and the use of technology can be a solution. In conclusion, PjBL is a strategic approach to strengthening scientific literacy while forming a critical, creative, and environmentally conscious generation.